Stability and predictability of the classification of mild cognitive impairment as assessed by episodic memory test performance over time. - de Jager, C; Budge, M (2005)
This study aimed to address the criteria and the stability of the classification of MCI. The Foresight Challenge cohort of 157 community-dwelling volunteers was assessed on 3 visits at 2-year intervals with episodic, semantic and working memory tests. Subjective memory complaints were assessed with the CAMDEX. Of the cohort, 2% had dementia and 31% were classified with MCI at visit 3, 43% with stable impairment from Time 1. Thirteen percent of those with objective memory impairment at Time 1 or 2 improved to control status by Time 3. Episodic memory tests were predictive for MCI at all timepoints, as were tests for praxis and Graded Naming, while at Time 3 spatial span lost predictive value, but processing speed became predictive. Decline in processing speed was seen in control and MCI groups, while memory performance and MMSE decline occurred only in the MCI group. The use of combined memory test scores gave better sensitivity to MCI than single tests. Subjective memory complaints were positive for 79% of the MCI group and 62.5% of controls. These findings would suggest consideration of modification of current MCI criteria.